2001
DOI: 10.1159/000051260
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease and the Cerebellum: A Morphologic Study on Neuronal and Glial Changes

Abstract: Structural manifestations of Alzheimer’s disease (AD) including neuronal loss were investigated in 12 cases of AD and in 10 healthy age-matched controls, with focus on the cerebellum. Linear Purkinje cell (PC) density was measured in the vermis and cerebellar hemispheres. Neurons were also counted in the inferior olivary nucleus. In vermis of the AD cases, the mean PC number was significantly lower (p = 0.019) than in the controls. The neurons in the inferior olive were similarly fewer, though not significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 22 publications
3
60
0
1
Order By: Relevance
“…33 Diaschisis is the cerebellar reduction related to the atrophy of superior structures and is commonly observed at late stages of dementia. 13 The main hypothesis suggesting the implication of the cerebellum in dementia invokes a possible role for diaschisis, 13,23,30 but our results show that cerebellar volume reductions can be observed even at early stages of the disease. Moreover, there are reports that secondarily affected regions could present mild atrophy and no histopathological changes, 33 and this is what we investigated here.…”
Section: Cerebellar Morphology In Dementiamentioning
confidence: 52%
See 4 more Smart Citations
“…33 Diaschisis is the cerebellar reduction related to the atrophy of superior structures and is commonly observed at late stages of dementia. 13 The main hypothesis suggesting the implication of the cerebellum in dementia invokes a possible role for diaschisis, 13,23,30 but our results show that cerebellar volume reductions can be observed even at early stages of the disease. Moreover, there are reports that secondarily affected regions could present mild atrophy and no histopathological changes, 33 and this is what we investigated here.…”
Section: Cerebellar Morphology In Dementiamentioning
confidence: 52%
“…29 Previous studies have reported cerebellar abnormalities in dementia. 13,30,31 In neuropathological studies, neuronal shrinkage and loss are well known changes that accompany AD and are most notable in the temporoparietal neocortex, limbic system, and some neuronal groups such as the locus coeruleus of the brain stem and the basal nucleus of Meynert in the basal forebrain. 30 Morphological studies, conversely, have focused on the traditional neuropathological hallmarks of AD, such as amyloid plaques, neurofibrillary tangles, and amyloid angiopathy, 30 and little has been reported on neuronal loss and other structural changes in AD.…”
Section: Cerebellar Morphology In Dementiamentioning
confidence: 99%
See 3 more Smart Citations